Fractional statistical dynamics and fractional kinetics - Silva, J. L.; Kondratiev, Yu. G.; Kochubei, A. N. (Methods of Functional Analysis and Topology, 2016)
We apply the subordination principle to construct kinetic fractional statistical dynamics in the continuum in terms of solutions to Vlasov-type hierarchies. As a by-product we obtain the evolution of the density of particles in the fractional kinetics in terms of a non-linear Vlasov-type kinetic equation. As an application we study the intermittency of the fractional mesoscopic dynamics.